Thyroid-Disrupting Activities of Groundwater from a Riverbank Filtration System in Wuchang City, China: Seasonal Distribution and Human Health Risk Assessment. (7th January 2020) - Kong, Dongdong; Liu, Hedan; Liu, Yun; Wang, Yafei; Li, Jian
Abstract : The recombinant thyroid hormone receptor (TR) gene yeast assay was used to evaluate thyroid disruption caused by groundwater from the riverbank filtration (RBF) system in Wuchang City, China. To investigate seasonal fluctuations, groundwater was collected during three seasons. Although no TR agonistic activity was found, many water samples exhibited TR antagonistic activity. The bioassay-derived amiodarone hydrochloride (AH) equivalents ranged from 2.99 to 274.40  μ g/L. Water samples collected from the riverbank filtration system during the dry season had higher TR antagonistic activity. All samples presented adverse 3, 3′, 5-triiodo-L-thyronine (T3) equivalent levels, ranging from −2.00 to −2.12  μ g/kg. Following exposure to water samples with substantial TR antagonist activity, predicted hormonal changes in humans of different gender and age ranged from 0.65 to 1.48  μ g/kg of T3, being 47% to 231% of normal. No obvious difference was found between genders or among age groups. Overall, the results revealed that the RBF system could remove the thyroid-disrupting chemicals in the river water to some extent. Considering the varying degrees of risk to human health, further treatment is needed to remove the potential thyroid-disrupting chemicals in pumping water after riverbank filtration to ensure drinking water safety.